Extent of atrium with 1:1 electrogram activation predicts response to ablation of atrial fibrillation. (24th May 2021) - Ganesan, P; Bhatia, N; Rogers, AJ; Krummen, D; Wang, P; Clopton, P; Rappel, WJ; Narayan, S
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): US National Institutes of Health Background: Mechanisms associated with successful termination of persistent atrial fibrillation (AF) are still under debate. We sought to study the association between spatial extent of atrium with organized conduction and AF ablation success. We hypothesized that patients with large areas of atrium having 1:1 electrogram activation akin to 'atrial tachycardia' may have a higher likelihood of AF termination by ablation. Methods: In n = 40 AF patients, n = 20 had termination by ablation ("Term"), and the remaining did not have AF termination by ablation ("Non-term"). Basket catheters (64 poles) were used to record unipolar electrograms (EGMs) in one or both atrium. Ablation targeted localized rotational/focal regions, after which pulmonary vein isolation was performed. Unipolar EGMs of 4sec duration at each 2x2 electrode neighborhood within 8x8 catheter grid were processed using a statistical correlation technique to identify the duration of 1:1 activations. Any EGM activation cycle that had a correlation above 80% was considered to be 1:1. Duration of contiguous 1:1 cycles was determined as percentage of total duration (4 sec). Results: Spatial area of atrium (percentage of mapping field) and the corresponding 1:1 durations were assessed for patients in Term and Non-term groups. Fig A shows spatial 1:1 maps of a Term and a Non-term patient. Fig B shows examples of 1:1 and non-1:1 EGMs. Patients in Term group had higher average 1:1 atrial area than non-term group for any 1:1 duration (Fig C, 15 ± 22% vs 2 ± 4% with ≥70% 1:1 duration, p = 0.03). Positive and negative predictive values of duration≥70% for AF termination were 64.7%, and 75%, with specificity 60% and sensitivity 78.6%, exceeding clinical risk scores. Conclusion: Persistent AF atrium shows areas of organized 1:1 conduction. Larger 1:1 atrial areas were identified in patients in whom AF terminated by ablation. Future studies should investigate mechanistic bases of organized conduction in AF.